Assets and liabilities : refugees from Hungary and Egypt in France and in Britain, 1956-1960 - De Aranjo, Alexandre G. A. (2013)
This thesis investigates the reception and treatment of the refugees from Hungary and Egypt who arrived in France and in Britain after the Hungarian revolution and the Suez crisis. The thesis argues that the reception of the refugees from Hungary and from Egypt was primarily linked to the French and British immigration policies and influenced by the Cold War context.